Effect of stocking density and salinity on the growth and survival of golden Anabas fry - Zahari, Zaaim; Christianus, Annie; Ismail, Muhammad Fadhil Syukri (Green Wave Publishing, 2018)
Stocking density and salinity influence on the growth and survival of golden Anabas fry were studied. Experiments were carried out at Hatchery Unit, Institute of Bioscience, Universiti Putra Malaysia, Serdang Selangor, Malaysia. Growth parameters were measured once a month. While survival was monitored daily throughout the experimental period. Water quality such as temperature, dissolved oxygen (DO), pH, ammonia and nitrite were measured once a week prior to water change. During the study period, fry were fed to apparent satiation with commercial crumble diet (Cargill 6103) containing 34% crude protein. After 6 weeks of culture, fry were weaned on Starfeed 9910 (1mm) containing 32% crude protein. Feedings were carried out two times daily at 0830and 1700. In the stocking density experiment, 3 densities tested were 2, 3 and 4 fry/L. All treatments were conducted in triplicates in 10L plastic aquaria. Golden Anabas fry with wet weight of 1.02g weight and total length of 3.60cm were used in this experiment. As for salinity experiment, golden Anabas fry were cultured in water with salinities of 0, 5, 10 and 15 ppt, at stocking of 3 fry/L, in 8L aquaria. Statistical analysis showed that there were significant differences (p<0.05) in the growth between the treatments. The best growth recorded was in 2 fry/L, followed by 3 and 4 fry/L. As for salinity experiment, 0 ppt showed significantly better (p<0.05) growth as compared to the rest of the treatments. However, the percentage of survival was not significantly different (p>0.05) among the treatments. In conclusion, golden Anabas fry showed better growth when cultured at low stocking density (2 fry/L) and can tolerate up to 15 ppt salinity.